A Study of Cognitive Styles of Senior Secondary Students with Relation to Their Gender (International Journal of Scientific Research and Management (IJSRM), 2017)
Cognitive style refers to the preferred way individual processes information. Unlike individual differences in abilities, which describe peak performance, styles describe a person’s typical mode of thinking, remembering or problem solving. In teaching it is the most important variable affecting the students in academics. The present study is based on the cognitive styles of boys and girls of senior secondary students. Simple random sampling technique has been used to collect the sample. 50 boys and 50 girls of senior secondary school have been selected for the study purpose. For result analysis, the chi- square test has been used. Significant difference has been found between cognitive styles of Hence investigator feels that there is a need for the development of new instructional programs that could accommodate the unique styles of the individual students.